Penerapan Konsep Ekologi Industri Dengan Metode Life Cycle Assesment (LCA) Dalam Pengolahan Minyak Jelantah Hasil Produksi Kerupuk di PD. Putra Jaya (PRJ) Menjadi Sabun Cair - Marisha Septiani; Fathimah Azzahra; Lady’s Iasa Tamarani SP; Budiharjo (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to apply the concept of Industrial Ecology using the Life Cycle Assessment (LCA) approach in utilizing used cooking oil generated from the cracker production process at PD. Putra Jaya (PJR) as raw material for liquid soap manufacturing. The LCA approach is employed to trace and evaluate environmental impacts at each stage of the product life cycle, starting from the collection of used cooking oil, the filtration or purification process, formulation, and up to the liquid soap production process. The research results indicate that the utilization of used cooking oil can reduce the potential for environmental pollution. In addition, utilizing used cooking oil as the base material for liquid soap enhances resource efficiency and strengthens the implementation of Industrial Ecology principles. This process also has the potential to provide added economic value for MSMEs (Micro, Small, and Medium Enterprises).